Does the speed of adjustment in regulation and supervision affect financial stability in developing countries?. Issue 4 (11th November 2019) - Azmeh, Chadi
Abstract : Purpose: This paper aims to examine the impact of bank regulation and supervision on financial stability. Financial sector reform, especially in developing countries, takes the form of a sudden adjustment in regulation and supervision. The main objective of the paper is to examine whether this fast and sudden adjustment in regulation and supervision has an undesirable impact on financial stability. Furthermore, the paper examines the role of real economic development in determining the impact of financial reform on financial stability. Design/methodology/approach: Empirically, on a sample of 57 developing countries over the period 2000-2013, the author explored the impact of bank regulation and supervision on financial stability for different sub-groups of countries. The division is based on the real level of economic development and, most importantly, on the speed of adjustment in regulation and supervision. The study uses the cross-sectional–ordinary least square model. Each country has three observations (average 2000-2004, average 2005-2008 and average 2009-2013), which are convenient, with the date of the three surveys on regulation and supervision (2002-2006-2011). The period of the averages is selected to cover periods before and after the survey as regulation and supervision may be adopted before the survey and as its impact may persist for the period after. Findings: The major finding of this study is that it supports the important role of the speed of adjustment in regulation and supervision, and its impact on financial stability. Soft adjustment in regulation and supervision has more positive impact on financial stability than fast adjustment. Activity restrictions have positive and significant impact on financial stability in soft adjustment countries' group. On the other hand, in countries with fast adjustment, results show negative and statistically significant impact on financial stability, especially for supervisory independence. More time is needed for supervisors to adapt to new regulation and supervision and gain expertise to monitor financial condition of banks in a consistent manner. Results also show that the level of economic development is an important factor when testing the impact of regulation and supervision on financial stability. In lower income countries, more room is available for corruption in lending, which has a negative impact on financial stability. Practical implications: This study advocates the necessity of taking the speed of adjustment in regulation and supervision by policymakers in developing countries, while initiating reform in the financial sector. Financial sector reform that takes the form of a sudden adjustment in regulation and supervision may have undesirable results in terms of financial stability. On the other hand, soft adjustment in regulation and supervision, which gives more room for supervisors to adapt and gain expertise, may have more positive impact on financial stability. Originality/value: This paper is the first paper to explore new methods of calculating the speed of adjustment in regulation and supervision, and to examine whether the high speed of financial reform in developing countries has an undesirable impact on financial stability.